1995
DOI: 10.1016/0735-1097(94)00359-x
|View full text |Cite
|
Sign up to set email alerts
|

Observations suggesting a high incidence of exercise-induced severe mitral regurgitation in patients with mild rheumatic mitral valve disease at rest

Abstract: Patients with exertional dyspnea and mild mitral stenosis and regurgitation at rest demonstrate a marked increase in pulmonary artery systolic pressure and mean transmitral pressure gradient during dynamic exercise. In a subset of these patients, marked worsening of mitral regurgitation appears to be the underlying mechanism of this hemodynamic deterioration. Because of the small sample size, this novel observation must be considered preliminary with respect to the true prevalence of exercise-related developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…In symptomatic patients in whom the severity of MR is estimated to be only mild at rest, exercise echocardiography may be useful in elucidating the cause of symptoms by determining whether the severity of MR increases or pulmonary arterial hypertension develops during exercise (54). It is noteworthy that the data supporting this concept were derived in patients with rheumatic MR, and the data supporting this application for degenerative MR are limited.…”
Section: Mitral Regurgitation (Mr)mentioning
confidence: 90%
“…In symptomatic patients in whom the severity of MR is estimated to be only mild at rest, exercise echocardiography may be useful in elucidating the cause of symptoms by determining whether the severity of MR increases or pulmonary arterial hypertension develops during exercise (54). It is noteworthy that the data supporting this concept were derived in patients with rheumatic MR, and the data supporting this application for degenerative MR are limited.…”
Section: Mitral Regurgitation (Mr)mentioning
confidence: 90%
“…8,12 Of note, MR severity increases by one grade (from moderate to severe, by measuring the proximal isovelocity surface area) in 30% of all patients during exercise. 8,34 This phenomenon is often associ ated with exercise induced pulmonary hypertension. 10 Patients with a marked increase in regurgitant volume or who develop pulmonary hypertension (defined as sys tolic pulmonary artery pressure >60 mmHg) during exer cise have lower symptom free survival than those who do not experience significant changes in MR and systolic pulmonary artery pressure during exercise.…”
Section: Fluctuating Degenerative Primary Mrmentioning
confidence: 99%
“…Direct rheumatic involvement of the tricuspid valve usually produces tricuspid stenosis as well as regurgitation; severity of either may necessitate intervention. Successful detection of TVR preoperatively may require dynamic physiologic assessment, as several investigations have shown that exercise may induce significant pulmonary hypertension not detected at rest [8,9].…”
Section: Opinion Statementmentioning
confidence: 99%